2013
DOI: 10.1016/j.jcrs.2013.05.036
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of prophylactic intracameral moxifloxacin injection in Japan

Abstract: Intracameral moxifloxacin (50 to 500 μg/mL) administration decreased the risk for endophthalmitis by 3-fold. In more than 18,000 cases, moxifloxacin administration of 500 μg/mL or less did not result in severe complications, such as toxic anterior segment syndrome or corneal endothelial cell loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(66 citation statements)
references
References 17 publications
0
62
0
4
Order By: Relevance
“…Matsuura et al [43] reported the incidence of endophthalmitis in the 4 years prior and 4 years following routine the use of intracameral moxifloxacin for prophylaxis of endophthalmitis in a Japanese hospital system. The incidence of endophthalmitis was one in 1955 cases prior to use of intracameral moxifloxacin and one in 6265 cases after, reflecting a three-fold decreased incidence.…”
Section: Postoperative Complications: Endophthalmitismentioning
confidence: 99%
“…Matsuura et al [43] reported the incidence of endophthalmitis in the 4 years prior and 4 years following routine the use of intracameral moxifloxacin for prophylaxis of endophthalmitis in a Japanese hospital system. The incidence of endophthalmitis was one in 1955 cases prior to use of intracameral moxifloxacin and one in 6265 cases after, reflecting a three-fold decreased incidence.…”
Section: Postoperative Complications: Endophthalmitismentioning
confidence: 99%
“…This was shown in 2007 in the randomized ESCRS trial (ESCRS Endophthalmitis Study Group 2007), and since then, the results have been replicated in several non-randomized studies (Wejde et al 2005;ESCRS Endophthalmitis Study Group 2007;Lundstrom et al 2007;Yu-Wai-Man et al 2008;Garat et al 2009;Anijeet et al 2010;Barreau et al 2012;van der Merwe et al 2012;Rosen 2012;Tatham & Brookes 2012;Friling et al 2013;Matsuura et al 2013;Myneni et al 2013;Rodriguez-Caravaca et al 2013;Shorstein et al 2013;Beselga et al 2014;Galvis et al 2014;Rudnisky et al 2014). This was shown in 2007 in the randomized ESCRS trial (ESCRS Endophthalmitis Study Group 2007), and since then, the results have been replicated in several non-randomized studies (Wejde et al 2005;ESCRS Endophthalmitis Study Group 2007;Lundstrom et al 2007;Yu-Wai-Man et al 2008;Garat et al 2009;Anijeet et al 2010;Barreau et al 2012;van der Merwe et al 2012;Rosen 2012;Tatham & Brookes 2012;Friling et al 2013;Matsuura et al 2013;Myneni et al 2013;Rodriguez-Caravaca et al 2013;Shorstein et al 2013;Beselga et al 2014;Galvis et al 2014;Rudnisky et al 2...…”
Section: Antibiotic Prevention Of Postcataract Endophthalmitismentioning
confidence: 89%
“…Thus, IC MFLX could prevent endophthalmitis in our model as well as IC LVFX. 42 The results of our study should be interpreted with care, considering its limitations. First, this study was conducted in a rabbit model with experimentally induced E. faecalis endophthalmitis.…”
Section: Figmentioning
confidence: 93%